Biomechanical Energy‐Driven Hybridized Generator as a Universal Portable Power Source for Smart/Wearable Electronics. Issue 12 (3rd February 2020) - Rahman, Muhammad Toyabur; Rana, SM Sohel; Salauddin, Md; Maharjan, Pukar; Bhatta, Trilochan; Park, Jae Yeong
Abstract: The fast growth of smart electronics requires novel solutions to power them sustainably. Portable power sources capable of harvesting biomechanical energy are a promising modern approach to reduce battery dependency. Herein, a novel elastic impact‐based nonresonant hybridized generator (EINR‐HG) is reported to effectively harvest biomechanical energy from diverse human activities outdoors. Through the rational integration of a nonlinear electromagnetic generator with two contact‐mode triboelectric nanogenerators, the proposed EINR‐HG generates hybrid electrical output simultaneously under the same mechanical excitations. By introducing a flux‐concentrator with a nanowire‐nanofiber surface modification, significant improvement in the energy harvesting efficiency of the EINR‐HG is achieved. After optimizing using simulations and vibration tests, the as‐fabricated EINR‐HG delivers an outstanding normalized power density of 3.13 mW cm −3 g −2 across a matching resistance of 1.5 kΩ at 6 Hz under 1 g acceleration. Under human motion testing, the EINR‐HG generates an optimal output power of 131.4 mW with horizontal handshaking. With a customized power management circuit, the EINR‐HG serves as a universal power source that successfully drives commercial smart electronics, including smart bands and smartphones. This work shows the massive potential of biomechanical energy‐driven hybridized generators for powering personal electronics and portable healthcare monitoring devices. Abstract : An elastic‐impact‐based nonresonant hybridized generator is designed for biomechanical energy harvesting at low frequency vibrations. Introducing a soft magnetic material‐based composite film as a flux‐concentrator and nanowire/nanofiber‐based triboelectric materials significantly improves the output performance of the hybridized generator. A customized power management circuit in the hybrid generator is designed to serve as a universal power source for smart electronics.